What can we learn from each other about undergraduate medical education in general practice / family medicine? - Zakarija-Grković (Zdravstveno varstvo, 2018)
Introduction There is a dearth of published literature on the organisation of family medicine/general practice undergraduate teaching in the former Yugoslavia. Methods A semi-structured questionnaire was sent to the addresses of 19 medical schools in the region. Questions covered the structure of Departments of Family Medicine (DFM), organisation of teaching, assessment of students and their involvement in departmental activities. Results Thirteen medical schools responded, of which twelve have a formal DFM. Few DFM have full-time staff, with most relying upon external collaborators. Nine of 13 medical schools have family doctors teaching other subjects, covering an average of 2.4 years of the medical curriculum (range: 1-5). The total number of hours dedicated to teaching ranged from 30 - 420 (Md 180). Practice-based teaching prevails, which is conducted both in city and rural practices in over half of the respondent schools. Written exams are conducted at all but two medical schools, with the written grade contributing between 30 and 75 percent (Md=40%) of the total score. Nine medical schools have a formal method of practical skills assessment, five of which use Objective Structured Clinical Examinations. Student participation is actively sought at all but three medical schools, mainly through research. Conclusion Most medical schools of the former Yugoslavia recognise the importance of family medicine in undergraduate education, although considerable variations exist in the organisation of teaching. Where DFM do not exist, we hope our study will provide evidence to support their establishment and the employment of more GPs by medical schools.
Keywords: dodiplomsko poučevanje; družinska medicina; države nekdanje Jugoslavije; family medicine; former Yugoslavia; general practice; Splitska iniciativa; splošna medicina; The Split Initiative; undergraduate teaching